Judicial Reduction of Penalties in Georgian Civil Law: Balancing Debtor and Creditor Rights - Rekhviashvili, Natia; Kharitonashvili, Nino (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Judicial discretion in the reduction of penalties plays a crucial role in balancing the interests of contracting parties under the Civil Code of Georgia. Specific Background: Article 420 grants courts the authority to reduce disproportionately high penalties, yet the lack of explicit legal criteria leaves room for case-by-case judicial interpretation. Knowledge Gap: Despite the volume of case law, there remains no standardized framework guiding courts in determining what constitutes an “inappropriately high” penalty. Aims: This study seeks to analyze Georgian court decisions to identify patterns and criteria employed when reducing penalties under Article 420. Results: The findings reveal that courts emphasize proportionality, reasonableness, and the specific circumstances of the breach, including the degree of fault and the scope of unfulfilled obligations. Moreover, the financial status of the parties and market expectations further influence judicial decisions. Novelty: This article consolidates judicial practices to offer a comprehensive framework for reducing penalties, contributing to both theoretical understanding and practical application in legal practice. It introduces a calculation methodology and suggests criteria for equitable penalty reduction in specific legal relationships. Implications: These insights will support legal practitioners in formulating fairer contracts, assist courts in maintaining contractual balance, and guide future legal reforms, fostering both justice and efficiency in contractual relationships.Highlights: Georgian courts use proportionality and reasonableness to reduce penalties under Article 420. The absence of explicit legal criteria allows case-by-case interpretation, ensuring flexibility but creating inconsistency. Financial status, market expectations, and fault degree influence the court’s discretionary decisions. Keywords: Penalty, Discretionary Power, Civil Code, Contractual Balance, Judicial Practice